EDUCATIONAL TECHNOLOGY FOR THE DEVELOPMENT OF PERCEPTIVE ABILITIES AIMED AT INCREASING THE SOCIAL ACTIVITY OF STUDENTS IN FUTURE TEACHERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In the developed countries of the world, there is a great experience in creating a new pedagogical system of training future teachers and applying it to practice. Pedagogical research of development is gaining importance. In particular, it is a vital pedagogical issue to discover social activity in students by paying attention to their inner spiritual aspects and educating them.